Financial Development and Energy Consumption Nexus in Nigeria: An Application of ARDL Bound Testing Approach - Ali, Hamisu Sadi; Yusop, Zulkornain Bin; Hook, Law Siong (International Journal of Energy Economics and Policy, 2015)
Using ARDL bound test framework, the dynamics of financial development, economic growth, energy prices and energy consumption was investigated in Nigeria for the period of 1972Q1-2011Q4. The finding signifies that variables were cointegrated as null hypothesis was rejected at 1% level of significance. In the short-run financial development has significant negative impact on fossil fuel consumption, economic growth also shows the same relationship. However, energy prices have positive and significant influence on the consumption of fossil fuel. In the long-run however, financial development has insignificant negative impact on energy consumption, and economic growth has negative but significant impact on energy consumption, while energy prices has positive and significant impact on fossil fuel consumption. The policy recommendation remains that Nigerian authority should try to explore other alternative sources of energy in order to curb the adverse effect of fossil fuel consumption on the financial market and overall economic growth. Exploring the potentials of green energy is paramount in Nigeria which is more eco-friendly and contain less carbon emissions Keywords: Financial development; Energy consumption; Oil prices. JEL Classifications: Q43